2010
DOI: 10.1007/s12272-010-0701-8
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of some novel benzimidazole derivatives for their potential anticonvulsant activity

Abstract: Selective GABA(A) receptor ligands are widely used clinically to reduce the occurrence of convulsions. Hence there is an intense interest in developing new benzimidazole derivatives demonstrating high selectivity and high affinity for GABA(A) receptors. With the purpose of designing new chemical entities with an enhanced binding affinity for GABA(A)/BZd receptor complex, we carried out a QSAR study on benzotriazine derivatives. We studied 28 potent GABA(A) receptor ligands; derivatives of benzotriazines, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…We speculate that the low EC 50 of NS1619 in this study may perhaps be explained by its possible GABAergic mechanism. Although no study has shown a link between NS1619 and GABA neurotransmission, other derivatives of benzimidazole were developed as GABA A ligands (Jain et al, 2010). In this study, we observed a significant potency shift of NS1619 under pentylenetetrazol, in a manner similar to flupirtine.…”
Section: Comparison Of Pharmacological Responses Within and Between Dmentioning
confidence: 47%
“…We speculate that the low EC 50 of NS1619 in this study may perhaps be explained by its possible GABAergic mechanism. Although no study has shown a link between NS1619 and GABA neurotransmission, other derivatives of benzimidazole were developed as GABA A ligands (Jain et al, 2010). In this study, we observed a significant potency shift of NS1619 under pentylenetetrazol, in a manner similar to flupirtine.…”
Section: Comparison Of Pharmacological Responses Within and Between Dmentioning
confidence: 47%
“…Benzimidazole and its derivatives are very important N‐containing heterocyclic compounds and are found in many naturally occurring products and various drugs . This is a very important class of compounds due to its wide spectrum of pharmaceutical and biological activities, such as anticancer, antimicrobial, antimalarial, anticonvulsant, and antifungal activity . In addition, substituted benzimidazole and its derivatives are the most important potential inhibitors of the parietal cell proton pump.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the benzimidazole derivatives are the bioisosters of natural nucleotides, which can interact easily with the macromolecules (proteins, enzymes and receptors) of the biological system, has made the benzimidazole and its derivatives as the privileged pharmacophore in drug discovery process [4,5]. They are able to produce anti-inflammatory [6], antibacterial [7], anti cancer [8], analgesic [9], antiviral [10] and anticonvulsant [11] activitie, etc., Further benzimidazoles also can act as inhibitors for α-Glucosidase [12], Cyclooxygenase [13], Poly (ADP-ribose) polymerase [14] and lysophosphatidic acid acyltransferase-β [15]. Interestingly, benzimidazoles are also being incorporated into various commercially available drugs [16,17].…”
Section: Introductionmentioning
confidence: 99%